The Use of Activated Carbon from Banana Peels and Cassava Peels in Reducing Iron (Fe) Contaminants in the Porong River in Sidoarjo - Muhammad Alvando Rahmantio; Muhammad Abdus Salam Jawwad (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to evaluate the effectiveness of activated carbon produced from banana peels and cassava peels in reducing iron (Fe) levels in the water of the Porong River, Sidoarjo. Activated carbon was produced through a carbonization process and chemical activation using a 15% H?PO? solution. Tests were conducted with varying column heights (20, 40, 60, 80 cm) and sampling times (30–150 minutes). The results showed that cassava peel activated carbon was more effective in removing Fe with a maximum removal percentage of 83.13% at a column height of 80 cm and a sampling time of 150 minutes, while banana peels reached 72.22%. This study proves the potential of organic waste as an environmentally friendly adsorbent for the remediation of water contaminated with heavy metals. Contribution to Sustainable Development Goals (SDGs):SDG 6  – Clean Water and SanitationSDG 12 – Responsible Consumption and ProductionSDG 9 – Industry, Innovation and InfrastructureSDG 14 – Life Below Water